######
17

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{ \displaystyle\left(\frac{1}{8}\right)^{-3}=
}\) \(\quad\)

######
18

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{ \displaystyle\left(\frac{1}{9}\right)^{-3}=
}\) \(\quad\)

######
19

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{\displaystyle {9x^{-12}}= }\)

######
20

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{\displaystyle {19x^{-3}}= }\)

######
21

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{\displaystyle {\frac{14}{x^{-4}}}= }\)

######
22

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{\displaystyle {\frac{8}{x^{-5}}}= }\)

######
23

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{\displaystyle {\frac{18x^{-9}}{x^{-26}}}= }\)

######
24

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle{\displaystyle {\frac{8x^{-11}}{x^{-17}}}= }\)

######
25

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle\frac{r^{-3}}{\left(r^{4}\right)^{10}}=\)

######
26

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle\frac{r^{-2}}{\left(r^{11}\right)^{7}}=\)

######
27

Rewrite the expression simplified and using only positive exponents.

\(t^{-11}\cdot t^{6}=\)

######
28

Rewrite the expression simplified and using only positive exponents.

\(t^{-5}\cdot t^{4}=\)

######
29

Rewrite the expression simplified and using only positive exponents.

\((9x^{-17})\cdot (6x^{6})=\)

######
30

Rewrite the expression simplified and using only positive exponents.

\((6x^{-10})\cdot (10x^{7})=\)

######
31

Rewrite the expression simplified and using only positive exponents.

\(\left(-5y^{-4}\right)^{-2}\)

######
32

Rewrite the expression simplified and using only positive exponents.

\(\left(-2y^{-16}\right)^{-3}\)

######
33

Rewrite the expression simplified and using only positive exponents.

\(\left(3y^{8}\right)^{4}\cdot y^{-22}=\)

######
34

Rewrite the expression simplified and using only positive exponents.

\(\left(3r^{3}\right)^{3}\cdot r^{-4}=\)

######
35

Rewrite the expression simplified and using only positive exponents.

\(\left(r^{4}t^{8}\right)^{-3}=\)

######
36

Rewrite the expression simplified and using only positive exponents.

\(\left(t^{6}y^{14}\right)^{-3}=\)

######
37

Rewrite the expression simplified and using only positive exponents.

\(\left(t^{-11}x^{10}\right)^{-3}=\)

######
38

Rewrite the expression simplified and using only positive exponents.

\(\left(x^{-4}r^{6}\right)^{-3}=\)

######
39

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle\left(\frac{x^{6}}{2}\right)^{-3}=\)

######
40

Rewrite the expression simplified and using only positive exponents.

\(\displaystyle\left(\frac{y^{15}}{4}\right)^{-4}=\)